a KAJIAN TEOLOGIS TENTANG PASTORAL KONSELING DALAM ALKITAB: Kajian Teologis, Pastoral Konseling, Alkitab - Steven Tubagus (Institut Agama Kristen Negeri Kupang, 2021)
Pastoral Counseling crisis is felt by everyone, lack of trust in counsellors. Based on this, it is necessary to contribute to Pastoral Counseling in guiding based on the Bible. Theological Study of Pastoral Counseling in the Bible. The purpose of this paper is to describe the Theological Study of Pastoral Counseling in the Theological Bible. Qualitative research using the descriptive biblical literature method by analyzing primary and secondary sources from books according to the topic of discussion. The result of the research is that Pastoral Counseling lays the foundation of the Bible, namely the word of God to everyone. Theological studies of pastoral counselling in the Bible consist of First. In the Old Testament, the word of God came to the prophets as people called by God personally to tell the word of God, a prophet did not deduct a word from what he had said. Spiritual guidance was given by Moses for the Israelites, not to grumble. Second. New Testament, Meeting with Jesus is to make someone honest, and there is a change, everyone when there is a conversation with Jesus his life will change, who used to sin now don't. Third. Bible analysis, God's Absolute Sovereignty and His wise revelation not only determine but also inspire and move people to worship Him. With His own initiative, God gives inspiration based on His sovereignty to reveal God's wisdom to humans, so that humans do His will, which is to come to worship and stay away from evil.